Australian women's financial security in later life: the effects of social structures and decision processes - Jefferson, Therese (Curtin University, 2005)
Existing studies provide a range of insights into the causes of womens low retirement incomes and emphasise the effect of low life-time incomes on womens access to economic resources in later life. Despite these insights, however, there is relatively little research on the roles played by motivations, social institutions and decision-making processes in determining womens capacity to save for retirement. In order to address some of these gaps in our understanding, this study aimed to broaden the range of theoretical approaches applied to economic studies of womens retirement savings strategies. Based on methodological perspectives informed by critical realism and feminist epistemology, the study utilised grounded research methods to collect and analyse qualitative data relevant to womens financial decisions and retirement plans. The data collection and analysis process are conceptually organised and integrated to propose a theoretical contribution that emphasises the links between social structures and specific decision-making processes that systematically contribute to low retirement savings for women. The studys findings are discussed with reference to existing economic literature that has not previously been utilised in studies of womens retirement incomes. The conclusions from this study suggest that there are significant features of womens decision-making contexts that contribute to ongoing under-saving to support women in later life.